The Use of Make A Match Method to Increase Mechanical Engineering Student’s Vocabulary - Syaefani Arif Romadhon; M. Taufik Qurohman (International Journal of English Linguistics, Literature, and Education (IJELLE), 2019)
The low understanding of machine student Vocabulary on machining terms in English requires an appropriate method to overcome them. This study aims to apply the use of Make A Match method to improve students learning outcomes in mastering Vocabulary. The subject in this study is students of Mechanical Engineering Study Program of Politeknik Harapan Bersama Tegal, about 30 students. The determination of this sample is based on the results of preliminary research on the class to be studied and the results of referrals from lecturers. While the object of this research is the effect of using the Make A Match learning method in Vocabulary mastery to increase student learning outcomes in English subjects. The implementation of the stages of activities carried out in 2 cycles. The research was carried out in the odd semester of the 2019/2020 academic year from November to December 2019. The first cycle was conducted in the third and fourth weeks of November while the second cycle was carried out in the fifth week of November and the first Sunday in January. This research is CAR consisting of two cycles with stages of planning, action, observation, and reflection. Both cycles use the application of the Make A Match learning model. Before the first cycle of learning is implemented to describe the initial conditions of students before getting action after the implementation of activities that end with evaluation activities through written tests for each cycle. The results of the research show that the initial ability of students before getting an action scores an average of 65 and a percentage of completeness of 60%. In cycle 1 there was an increase in the average value to 69 with a percentage of completeness of 75%. In cycle 2 there was an increase in the average score to 75 and the completeness reached 87%. And the results of the study showed an increase in achievement in English courses which was very significant, that is 87% of 30 students scored 70 in accordance with the specified minimum value. And student responses to the learning process are in the positive category.